Seminar of the Jewish Community and Communist Society (Attempt at Analysis of the Years 1948–1968) [Seminář židovská komunita a komunistická spoločnosť (pokus o analýzu rokov 1948–1968)].: Institute of Ethnology of the Slovak Academy of Sciences and the Holocaust Documentation Center, 20th–21st April 2009, Bratislava, Slovakia. - Soukupová, Blanka (Lidé města, 2009)
The first day of the spring Bratislava seminar took place in the framework of the solution to the problem Reflections of totalitarian systems – relation of the Jewish community and state power after 1945 (head of project, Peter Salner, assistant head, Blanka Soukupová), which is one of the main goals of the Ethnological Institute of the Slovak Academy of Sciences. In his introduction, Peter Salner summarized the consequences of the Shoah for the Jewish community in Czechoslovakia (lessening of their number, unfortunate changes of its demographic structure generally, change of its value orientations, necessity and for the first time in history also the possibility [!] of choosing further strategies of the future).